Molecular and morphological characterization of fungi isolated from nutmeg (Myristica fragrans) in North Sulawesi, Indonesia - FITRI ARIFAH; LUQMAN QURATA AINI; ANTON MUHIBUDDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Arifah F, Aini LQ, Muhibuddin A. 2023. Molecular and morphological characterization of fungi isolated from nutmeg (Myristica fragrans) in North Sulawesi, Indonesia. Biodiversitas 24: 441-453. Nutmeg (Myristica fragrans Houtt) is one of the predominant commodities from Indonesia exported to the EU market. However, it is frequently rejected due to mycotoxin (especially aflatoxin) content exceeding the aflatoxin standard set by the EU. The high levels of aflatoxin were hypothesized to be produced by a toxigenic fungus infecting nutmeg during and after harvest. The study aims to determine and identify fungal contaminants in nutmeg kernels and provide information on the types of mycotoxins produced. Ten fungal morphotypes were isolated from nutmeg kernels collected from North Minahasa, North Sulawesi, Indonesia, and were grouped into four genera (Aspergillus, Lasiodiplodia, Rhizopus, and Penicillium) based on morphological characters. Ten fungal morphotypes were identified, i.e., Aspergillus flavus (Groups I and II), A. tamarii (Groups I and II), A. niger, A. aculeatus, A. ochraceus, Lasiodiplodia sp., Rhizopus delemar, and Penicillium sp. Isolates of A. flavus and A. tamarii were divided into two groups based on slight differences in their colony appearances. Molecular identification using homology of 18S rDNA sequences and ITS regions supports morphological identification except for isolates of A. flavus (Groups I and II), Lasiodiplodia sp., and Penicillium sp. These isolates were identified as A. nomiae and A. aflatoxiformans (A. autswikcii), L. theobromae, and P. citrinum. The maximum likelihood phylogenetic tree showed that isolates from the same species were grouped in the same clade. The L. theobromae was the most dominant type of fungus in the nutmeg kernels (55.61%), followed by A. niger (23.8%) and A. tamarii (10.53%). It is the first report of A. aflatoxiformans or A. autswikcii in nutmeg kernels, and no incidence of L. theobromae in nutmeg kernels from Indonesia previously.